Differential DNA Methylation of Human Metastable Epialleles in Guatemalan Infants at Birth Due to Timing of a Maternal Lipid-Based Nutrition Supplement and Pre-Pregnancy BMI (P11-139-19). (13th June 2019) - Borengasser, Sarah; Hendricks, Audrey; Jambal, Purevsuren; Gilley, Stephanie; Palacios, Alexandra; Kemp, Jennifer; Westcott, Jamie; Garces, Ana; Figueroa, Lester; Friedman, Jacob; Jones, Kenneth; Hambidge, Michael; et al.
Abstract: Objectives: Human metastable epialleles (MEs) are specific regions that are systemically methylated (lack tissue specificity), stable over time, and variably expressed between individuals. DNA methylation (DNAme) of MEs have been previously reported to be altered by maternal nutritional status at the time of conception. Here, we examined DNAme of MEs from a subset of Guatemalan mother/infant dyads as part of the Women First study, an international RCT that tested whether timing of a daily lipid-based nutrition supplement (LNS) improved birth length. The 3 study arms are: women consumed LNS ≥ 3 months prior to conception until delivery (Arm 1, N = 45); women consumed the same LNS commencing at 12 weeks gestation until delivery (Arm 2, N = 45); or no LNS (Arm 3, N = 44). The purpose of this study was to test if the timing of maternal LNS and pre-pregnancy BMI (ppBMI, BMI range = 20.1 – 38.4 kg/m 2 ) led to differential DNAme of MEs in infants at birth. Methods: Bisulfite-converted DNAme libraries were constructed using NimbleGen SeqCap Epi CpGiant probes from amnion tissue collected at birth. Individuals were sequenced via 2 × 150 paired end reads using the Illumina NovaSeq sequencer. Subjects that passed quality control (131/142 subjects) were used in subsequent statistical analyses. A linear model was used to test for the interaction between maternal LNS and ppBMI on infant DNAme for each base pair site within 296 previously identified candidate ME regions. The number of methylated base pairs per region ranged from 1 – 737. A significance level adjusting for the 296 regions was set at P  ≤ 0.000169. Results: We identified 6 ME regions with significant interactions, demonstrating differential ME DNAme due to intervention arm was dependent on ppBMI values. Our analyses also identified 3 CpGs associated with ppBMI regardless of LNS status and 1 CpG associated with LNS regardless of ppBMI suggesting a role for independent effects of maternal LNS and ppBMI on ME DNAme. Conclusions: Our findings indicate that timing of maternal LNS and ppBMI contribute to DNAme of candidate MEs in infants at birth, suggesting epigenetic influences due to in utero exposures. Future analyses will identify genes associated with changes in ME DNAme and the role of DNAme on infant growth. Funding Sources: Bill & Melinda Gates Foundation and National Institutes of Health.